Hydrolysate of ovalbumin: production and evaluation of the functional properties of peptides - S. D. Zhamsaranova; S. N. Lebedeva; B. A. Bolkhonov; D. V. Sokolov; B. A. Bazhenova (Теория и практика переработки мяса, 2023)
Chicken eggs proteins and their derivatives, like protein hydrolysates, peptides and amino acids, possess high nutritional value and provide a wide range of biological activity. They serve as sources for development of functional ingredients that draw the attention of specialists in the food production and biomedical industries, as well as the livestock feed industry. Enzymatic hydrolysis of proteins is a popular process for obtaining bioactive peptides with multifunctional properties. The purpose of this study is to obtain a hydrolysate of ovalbumin with a high degree of hydrolysis and to determine its functional and technological parameters. The research presents a two-stage scheme of ovalbumin hydrolysis with the help of pepsin and trypsin which provide high degree of hydrolysis (82–83%). The fractional composition of the hydrolysate is determined. The fractional composition is represented by three main fractions (high, medium and low molecular weight). The summarized antioxidant activity (SAA) of the hydrolysate is considered within the dynamics of the hydrolysis process. The highest SAA value was noted after 2 hours, and it amounted to 170.23 mg/l; at the end of hydrolysis the SAA value was equal to 114.31 mg/l. When analyzing the SAA, it was found that the main contribution to the summarized antioxidant activity of the ovalbumin hydrolysate is made by peptides of the medium molecular fraction. The microfiltration process, used in the research, made it possible to separate high-molecular compounds, which led to an increase in the SAA of the hydrolysate to 189.9 mg/l. The main functional and technological parameters of the hydrolysate are determined in this research. The comprehensive study of the biological activity and functional characteristics of egg protein hydrolysates and their peptides provides a theoretical basis for expanding the range of functional ingredients obtained from food proteins and for replenishing the range of functional foods.